Palp-Faction: An African Milkweed Dismembers Its Wasp Pollinators. Issue 3 (26th August 2014) - Shuttleworth, Adam; Johnson, Steven D.
Abstract : Interactions between pollinators and nectar-producing flowers are usually assumed to be mutualistic, but the exploitative basis of these relationships can lead to antagonistic interactions. Flowers of the African milkweed, Pachycarpus appendiculatus E. Mey, produce concentrated nectar that is consumed primarily by the large spider-hunting wasp Hemipepsis dedjas Guerin (Hymenoptera: Pompilidae). Pollinaria of this milkweed become attached to the palps of these wasps during nectar feeding. Broken wasp palps were found between guide rails, attached to corpuscula that were trapped behind the guide rails, and attached to pollinia that were inserted into the stigmatic chambers of the flowers. Approximately 85% of wasps captured on flowers of P. appendiculatus were missing one or more palps, whereas only 9% of wasps captured on flowers of another asclepiad species were missing any palps. It thus seems that wasps face a high risk of losing their palps when foraging on these flowers. The interaction may thus be antagonistic for the wasps if the cost of losing their sensory palps (not yet established) is greater than the benefits of the nectar reward. The plants, however, gain clear benefit from the interaction, as verified by the removal and insertion of pollinia in flowers exposed solely to visits by pompilid wasps.